Evolution of Development Centres in the Military Sector – from Beginnings to Game Changers - Czainska, Katarzyna; Balcerzyk, Dorota; Balcerzyk, Robert (Ewolucja ośrodków rozwoju w sektorze wojskowym – od początków do game changers, 2023)
The article presents the results of the review of literature and source materials (military and civilian), the purpose of which was to determine: diagnosed competencies, applied methods of diagnosis and their effectiveness using Assessment/Development Centres. The study covered materials from 1920 to 1974, including declassified documents from experiments carried out in the German, British, Danish and American armies. The obtained results were confronted with selected methods of officer development currently used in the Polish army. It was found out that the centre are mainly used in working with officers, and the subject of the diagnosis is primarily leadership competencies (defined by the performance dimension). Since the 70s of the 20th century the basic principles of the organization of the centres have not changed, namely the multidimensionality of the research, the complexity of the tools used and the collectivism of the assessment. Game changers in this field are the tools and forms of carrying out individual elements of assessment; solutions related to computerization, virtualization and neurodiversity are being implemented, examples of which are described in this study.
Czainska, K., Balcerzyk, D., and Balcerzyk, R. (2023). Evolution of Development Centres in the Military Sector – from Beginnings to Game Changers. In M. Hajdas (Ed.), Game Changers in Management (pp. 98-116). Wroclaw: Publishing House of Wroclaw University of Economics and Business.
Keywords: assessment centres; development centres; military training; centra oceny; centra rozwoju; szkolenia wojskowe